PENEGAKAN HUKUM LINGKUNGAN TERKAIT GALIAN C DI DESA SEBUDI KABUPATEN KARANGASEM - Mantra, Tria; Dirksen, A A Ngr Gd (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013, 2013)
Environment’s problems nowadays become hot issues among peoples, government or Social Organizations that focus on environment. Many environment damages occur because of activities done by the peoples or they happen because of the influences of the environment itself. In the research writing entitled “The Maintenance of Environment Rules Related to Sand Quarying in Sebudi Village, Karangasem Regency, there are some problems in quarrying area and how the efforts should be done if there are violations of a rule in the quarrying activities. There are three efforts, administratif, civil and criminal sanctions. The method used in this research is Empirical Method. Finally, in Sebudi Village, there are many violations in the quarrying area that can damage the environment in the future.
Keywords: environment, influence, government, society